2020
DOI: 10.3390/jcm10010030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cellular Regulatory Factors before and after Decompression of Odontogenic Keratocysts

Abstract: Decompression followed by enucleation, which is one of the treatments used for odontogenic keratocysts (OKCs), is frequently used in OKC lesions of large sizes. This method offers the advantage of minimizing the possibility of sensory impairment without creating a wide-range bone defect; moreover, the recurrence rate can be significantly lower than following simple enucleation. This study aimed to assess the changes in histology and expression of proliferation markers in OKCs before and after decompression tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…[ 16 ] Park et al . [ 17 ] suggested that the aggressiveness and biological behaviour of the cystic lining does not change after decompression in odontogenic keratocysts. It is reported that there is no significant association between cystic cavity reduction rate and pathological type of jaw cyst.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Park et al . [ 17 ] suggested that the aggressiveness and biological behaviour of the cystic lining does not change after decompression in odontogenic keratocysts. It is reported that there is no significant association between cystic cavity reduction rate and pathological type of jaw cyst.…”
Section: Discussionmentioning
confidence: 99%
“…This study was initially approved by the Research Ethics Committee of Hospital de Clínicas de Porto Alegre (2019/0337) CAAE 15329119.9.0000.5327 with the objective to verify the expression of BGN in breast tissues with and without cancer, using the D-HSCORE method [3] . The Research Ethics Committee waived the Informed Consent Form because the breast samples were older than 5 years.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…TNFRSF17 immunoreactivity was quantified in three randomly selected representative slide areas (×400 magnification) using a light microscope. The percentage of TNFRSF17-positive area out of the total area was calculated (23,24,(26)(27)(28).…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%